Synthesis of Electronic Frequency Tuning Units for Narrowband Ultra-Low Noise Oscillators with Surface Acoustic Waves Resonators - V. A. Loiko; A. R. Safin; A. A. Boburkov (Известия высших учебных заведений России: Радиоэлектроника, 2024)
Introduction. Modern radio engineering systems impose strict requirements on the stability of the frequency of microwave oscillation sources (microwave generators) included in their composition. However, microwave oscillators (on dielectric resonators or resonators on surface acoustic waves), despite the low levels of power spectral density of frequency fluctuations of the generated signals, fail to exhibit the frequency stability required for most precision applications (phase noise meters, aircraft radars, ultra-low-noise frequency synthesizers). It is possible to increase the frequency stability of such oscillators, e.g., by using of a phase-locked loop system; however, for its implementation, as a rule, an electronic frequency tuning unit should be included in the microwave oscillator. The introduction of such a unit into the microwave oscillator can lead to degradation of its other electrical characteristics, e.g., the power spectral density of frequency fluctuations of the generated signals.Aim. Development of a method for synthesizing electronic frequency tuning blocks with the required range of introduced phase shift and minimal intrinsic power loss for narrow-band microwave oscillators with resonators based on surface acoustic waves.Materials and methods. The synthesis of electronic frequency tuning blocks is carried out by a numerical-analytical method using the MATLAB (academic license no. 906991) environment. The obtained results are analyzed by a comparative method.Results. The paper presents a methodology for synthesizing electronic frequency tuning blocks with the required range of changes in the introduced phase shift while maintaining minimal insertion losses, which makes it possible to consider the intrinsic parasitic parameters of the varactor. Recommendations on the correct choice of varactors are given. A comparative analysis of calculated and practical results is carried out. The electronic frequency tuning unit was implemented on the basis of "Radiocomp" in 2023.Conclusion. The presented methodology for synthesizing electronic frequency tuning blocks is versatile and can be used not only for the synthesis of electronic frequency tuning blocks of various narrow-band microwave oscillators using twoport resonators as a frequency-setting element, but also for the synthesis of narrow-band microwave phase shifters.